“Efectos de la aplicación edáfica de potasio y boro, en el cultivo de cacao (Theobroma cacao L.), sobre el desarrollo y rendimiento de la mazorca en la zona de Puebloviejo.” - Gil Reyes, Narcisa Elizabeth (2018)
VII. SUMMARY The present experimental work was carried out in the properties of Hacienda la Libertad. Located at km 4.5 on the road Puebloviejo - Catarama, province of Los Ríos. Its objective was to evaluate the effects of edaphic potassium and boron applications in the development and yield of the cocoa crop (Theobroma cacao L.), in the area of Puebloviejo, Los Ríos. The sowing material used was the clone "CCN-51" of 5 years of planting, the nutrients Potassium (K2O) and Boron (B2O3) were evaluated, in different doses and mixtures between both fertilizers, distributed in nine treatments and three repetitions, and the randomized complete blocks experimental design was used. The mean comparisons were made with the Tukey test at 5% significance. For optimal growth of the crop, the necessary field work was carried out, among which are irrigation, fertilization, phytosanitary control, weed control and harvesting. In addition, the variables diameter of the ear, number of ears per plant, length of ear, average weight of the ear, number of seeds per ear, weight of the grain, weight of 100 seeds, yield and economic analysis were evaluated. The results obtained determined that the applications of different doses of Potassium and Boron, allow to obtain significant increases of these nutrients in the soil. The application of 40 g B2O3 per plant, showed the best results and influenced directly to obtain the highest values in the variables average weight of the ear, number of seeds per ear, weight of the grain, length of ear and weight of 100 seeds. The variables length of ear to week 5 and number of ear per plant did not show significant differences. The incorporation of 40 g B2O3 allowed to obtain the highest yield with 268 kg / ha and the highest net profit with $ 302.54. Palabra clave: cacao, fertilizante, potasio y boro.